Analysis of hyaluronan and its derivatives using chromatographic and mass spectrometric techniques - Šimek, Matěj; Lemr, Karel; Hermannová, Martina; Havlíček, Vladimír (Carbohydrate polymers, 2020)
The aim of this paper is to review chromatographic and mass-spectrometric methods and underline the best analytical approaches for successful analysis of various hyaluronic acid species in different types of samples. Hyaluronan-degrading enzymes and chemical depolymerization produce di- or oligosaccharides suitable for hyaluronan quantification or structural characterization of hyaluronan derivatives. Efficient purification and pre-column derivatization of hyaluronan disaccharides by reductive amination allow subnanogram quantification in biological samples. The chromatographic separation is capable to distinguish all glycosaminoglycans disaccharides and to resolve hyaluronan fragments with 2-40 monomers. Using electrospray ionization or matrix assisted laser desorption ionization, hyaluronan fragments up to 8 kDa or 41 kDa, respectively, can be observed. One- or two-dimensional chromatographic separation with higly sensitive mass-spectrometric detection is an indispensable tool for revealing substituent position, extent of modification and substitution patterns of chemically modified hyaluronan derivatives. It is essential for studying structure-biological function relationships of hyaluronan and its derivatives.
Keywords: Mass spectrometric analysis; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Glycosaminoglycans; kyselina hyaluronová; Liquid chromatography analysis; hmotnostní spektrometrie s elektrosprejovou ionizací; Hyaluronic Acid; aminace; Hyaluronic acid; Amination; Spectrometry, Mass, Electrospray Ionization; Oligosaccharides; Polysaccharide derivative